Bleomycin Sclerotherapy for Severe Symptomatic and Persistent Pelvic Lymphocele - Ana Sofia Fernandes; Antónia Costa; Raquel Mota; Vera Paiva (Case Reports in Obstetrics and Gynecology)
Background. Pelvic lymphoceles are frequently described as a complication of pelvic lymphadenectomy performed for surgical staging of gynaecologic malignancies. Case Report. A 72-year-old woman presented with severe symptomatic and refractory lymphocele associated with persistent lower limb lymphedema and recurrent erysipelas. After four CT fluoroscopy scan guided percutaneous catheter drainages, the lymphocele complicated with infection finally resolved with two sessions of bleomycin sclerotherapy. Conclusion. Symptomatic persistent lymphoceles require treatment and nowadays the first option is interventional radiologic procedures. Bleomycin is a safe and effective sclerosing agent and therefore should be regarded as a first-line treatment choice.